ABNORMAL SHOOT 6 interacts with KATANIN 1 and SHADE AVOIDANCE 4 to promote cortical microtubule severing and ordering in Arabidopsis. Issue 4 (2nd October 2020) - Li, Yuanfeng; Deng, Meng; Liu, Haofeng; Li, Yan; Chen, Yu; Jia, Min; Xue, Hui; Shao, Jingxia; Zhao, Jun; Qi, Yafei; An, Lijun; Yu, Fei; et al.
Abstract: Plant interphase cortical microtubules (cMTs) mediate anisotropic cell expansion in response to environmental and developmental cues. In Arabidopsis thaliana, KATANIN 1 (KTN1), the p60 catalytic subunit of the conserved MT‐severing enzyme katanin, is essential for cMT ordering and anisotropic cell expansion. However, the regulation of KTN1‐mediated cMT severing and ordering remains unclear. In this work, we report that the Arabidopsis IQ67 DOMAIN (IQD) family gene ABNORMAL SHOOT 6 ( ABS6 ) encodes a MT‐associated protein. Overexpression of ABS6 leads to elongated cotyledons, directional pavement cell expansion, and highly ordered transverse cMT arrays. Genetic suppressor analysis revealed that ABS6‐mediated cMT ordering is dependent on KTN1 and SHADE AVOIDANCE 4 (SAV4). Live imaging of cMT dynamics showed that both ABS6 and SAV4 function as positive regulators of cMT severing. Furthermore, ABS6 directly interacts with KTN1 and SAV4 and promotes their recruitment to the cMTs. Finally, analysis of loss‐of‐function mutant combinations showed that ABS6, SAV4, and KTN1 work together to ensure the robust ethylene response in the apical hook of dark‐grown seedlings. Together, our findings establish ABS6 and SAV4 as positive regulators of cMT severing and ordering, and highlight the role of cMT dynamics in fine‐tuning differential growth in plants. Abstract : The organization of cortical microtubule arrays controls the direction of cell expansion in plants. Two previously unknown, plant‐specific positive regulators of cortical microtubule severing and ordering, ABNORMAL SHOOT6 and SHADE AVOIDANCE4, along with the microtubule severing enzyme KATANIN1, act together to promote microtubule ordering and directional cell expansion.